Seni Menangani Keluhan Pasien: Strategi Komunikasi Interpersonal untuk Tenaga Kesehatan di Rumah Sakit Permata Bunda Yogyakarta - siswatibudi, harpeni; Rahmad Hidayat, Anas; Nugroho, Haryo; Wibowo, Marsiana (Permata Indonesia, 2025)
Healthcare services at Permata Bunda Hospital in Yogyakarta face challenges in handling patient complaints, which impact hospital satisfaction and image. Complaint handling techniques training was conducted to equip medical personnel and service staff with effective communication, empathy, analysis, and problem-solving skills to handle patient complaints professionally. The training, conducted on July 14, 2025, included communication materials, simulations, case studies, and role-plays, with evaluations using observation and short quizzes. The training results demonstrated a significant improvement in participant skills, with complaint response times reduced from 24 hours to less than 6 hours and patient satisfaction increasing from 65% to 92%. This training reinforced a culture of excellent service and continuously improved service quality. It is recommended that training be conducted regularly and that a complaint monitoring system be developed for effective follow-up. Strengthening the complaint handling team and supporting facilities also needs to be improved. Keywords: complaint handling; training; Interpersonal communication; patient satisfaction; healthcare